2021
DOI: 10.1021/acsptsci.1c00047
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Preservative Removal from Commercial Insulin Formulations Reduces Tissue Inflammation while Maintaining Euglycemia

Abstract: Background: Exogenous insulin therapy requires stabilization of the insulin molecule, which is achieved through the use of excipients (e.g., phenolic preservatives (PP)) that provide protein stability, sterility and prolong insulin shelf life. However, our laboratory recently reported that PP, (e.g., m-creosol and phenol) are also cytotoxic, inducing inflammation and fibrosis. Optimizing PP levels through filtration would balance the need for insulin preservation with PP-induced inflammation. Method: Zeolite Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…5,23,24 The inflammatory process changes dynamically over wear time due to ongoing tissue trauma caused by the cannula and proinflammatory insulin and insulin preservatives (eg, m-Cresol). 6,7,25,26 The evidence of the impact of preservatives on the inflammatory tissue response is conflicting, as it has been shown that a decrease of preservatives is associated with the formation of insulin aggregates (fibrils) which are known to increase inflammation. [27][28][29] In contrast, a recent well-designed IIS study in diabetic swine concluded that the insulin molecule itself is the major pro-inflammatory agent when infused into the SC tissue, rather than the excipients.…”
Section: Discussionmentioning
confidence: 99%
“…5,23,24 The inflammatory process changes dynamically over wear time due to ongoing tissue trauma caused by the cannula and proinflammatory insulin and insulin preservatives (eg, m-Cresol). 6,7,25,26 The evidence of the impact of preservatives on the inflammatory tissue response is conflicting, as it has been shown that a decrease of preservatives is associated with the formation of insulin aggregates (fibrils) which are known to increase inflammation. [27][28][29] In contrast, a recent well-designed IIS study in diabetic swine concluded that the insulin molecule itself is the major pro-inflammatory agent when infused into the SC tissue, rather than the excipients.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed towards the development of buffer-free and preservative-free formulations. It has been recently suggested that the removal of phenolic preservatives from the commercially available insulin products before SC injection by using Z-Y filtration reduces the inflammatory reactions induced by repeated SC injections ( 146 , 147 ). Finally, alternative buffers and preservatives should be explored and studied for use in the development of future formulations.…”
Section: Discussionmentioning
confidence: 99%
“… Their Review ingeniously combines information from cell, animal, and clinical studies to explain the multifaceted pharmacology of metformin. Mulka et al contributed a research article on improving the safety of commercial insulin formulations . The authors found that after removal of the phenolic preservative, tissue inflammation was reduced without loss of efficacy.…”
Section: Pharmacology and Safety Of Approved Diabetes Drugsmentioning
confidence: 99%
“…Mulka et al contributed a research article on improving the safety of commercial insulin formulations. 6 The authors found that after removal of the phenolic preservative, tissue inflammation was reduced without loss of efficacy.…”
mentioning
confidence: 99%